NAWENDIWIN: The art of being related - Anishinaabeg Kinship-centred Governance and Family law (Nawendiwin) Report - Williamson, Tara; Owen, Simon; Arnold-Cunningham, Cheyenne (Indigenous Law Research Unit, 2022)
Niijkiwendidaa Anishnaabekwewag Services Circle, Law Foundation of Ontario, and McConnell Foundation Faculty Unreviewed